Differential diagnosis and long-term outcomes of non-atrophic duodenal changes in children - Kröger, Sofia; Repo, Marleena; Hiltunen, Pauliina; Vornanen, Martine; Huhtala, Heini; Kivelä, Laura; Kurppa, Kalle (Frontiers in Pediatrics, 2022)
Objectives and study Gastrointestinal endoscopy is often performed when investigating abdominal complaints in children. While atrophic changes of the duodenal mucosa are usually caused by celiac disease, the prevalence and clinical significance of non-atrophic duodenal changes are less clear. We studied these issues in a large pediatric endoscopic cohort. Methods Comprehensive data on clinical features, diagnostic findings and long-term outcomes of children who had undergone upper gastrointestinal endoscopy with systematic duodenal sampling were collected. Study variables were compared between children with non-atrophic changes and normal histology, and between those with non-atrophic changes who did and did not receive a diagnosis. Results The study comprised 1,170 consecutive children, of whom 51 (4.4%) had non-atrophic and 315 (26.9%) atrophic duodenal changes and 804 (68.7%) normal histology. The most common non-atrophic findings were non-specific inflammation (n = 19) and intraepithelial lymphocytosis (n = 14). Patients with non-atrophic changes presented more often with blood in stools (23.5 vs. 11.3%; p = 0.009), anemia (43.2 vs. 36.5%; p = 0.028) and positive celiac serology (34.3 vs. 12.9%; p < 0.001) than those with a normal duodenum. Twenty-four (44%) of those with non-atrophic changes received an initial diagnosis, the most common of which were inflammatory bowel disease (IBD) (n = 8), Helicobacter pylori infection (n = 3) and food allergy (n = 3). The prevalence of the diagnoses did not differ from those with a normal duodenum. Those who received a diagnosis had more often blood in stools (37.5 vs. 11.1%; p = 0.027), anemia (70.6 vs. 20.0%; p = 0.002) and negative celiac serology (50.0 vs. 7.7%; p = 0.013) than those without diagnosis. During a follow-up of 6.1–13.3 years, five of the 12 initially undiagnosed seropositive patients developed celiac disease, and one patient also developed ulcerative colitis. Conclusion Non-atrophic duodenal changes are relatively common and associated with anemia, blood in stools, and positive celiac disease serology. Excluding potential celiac disease, those without an initial diagnosis have a favorable long-term prognosis.